Synthesis of Tungsten Carbide from Bacterial Cellulose. (27th April 2016) - Islam, Monsur; Martinez-Duarte, Rodrigo
Abstract : Here we present preliminary experiments for the synthesis of carbide material using bacterial cellulose as carbon source. We used bacteria cellulose available as Nata de Coco and infiltrated it with tungsten trioxide (WO3 ) nanoparticles. This composite was heat treated at 1300 °C in nitrogen atmosphere. The XRD pattern confirms the synthesis of tungsten carbide (WC) in the carbonaceous material, though a significant amount of metallic tungsten remained unreacted. SEM images shows that WC particles are present only at the surface of the carbon, which may be a consequence of improper infiltration or collapse of carbon matrix during heat treatment